Rehabilitasi Sosial dalam Pengembangan Self-Efficacy pada Disabilitas Netra - Siti I'anatun Nafi'ah; Alfin Miftahul Khairi (Ghaidan: Jurnal Bimbingan Konseling Islam dan Kemasyarakatan, 2023)
ABSTRAC:Everyone who has a visual impairment either totally or vaguely is called a blind person. Visual impairment causes blind people to have less motivation, are unsure of their abilities and are pessimistic about life. This makes the self-efficacy of blind people tend to be low. From this, blind persons are entitled to special treatment as regulated in Law no. 4 of 1997 article 6 namely social rehabilitation. Social rehabilitation is a program designed to improve physical, psychological and social disabilities. This study aims to determine social rehabilitation in the development of self-efficacy for visual sensory disabilities at RPS Bhakti Candrasa. This study uses a qualitative approach with a case study research method. The data collection is done by observation, interviews and documentation. The subjects in this study were 6 beneficiaries of RPS Bhakti Candrasa. The results in this study indicate that the process of the vocational guidance service program (ADL, Brille literacy, massage) and mobility orientation begins by introducing some basic theories which are grouped according to ability. In addition, social rehabilitation shows that it can develop self-efficacy for disabled blind RPS Bhakti Candrasa which is proven by the achievement of aspects of self-efficacy.